2020
DOI: 10.1111/ijfs.14875
|View full text |Cite
|
Sign up to set email alerts
|

Quality attributes of fufu in South‐East Nigeria: guide for cassava breeders

Abstract: Fufu is a popular traditional fermented wet paste food product from cassava. We examined consumer preferences and quality attributes of fufu in Abia and Imo States of SouthEast Nigeria, with special attention to gender differences, for the purpose of providing guidance to breeders. Data were analysed by the use of descriptive and inferential statistics. Participants for the interview were randomly selected from a list of farmers in the study area. Individual (II) interviews were conducted among 80 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 35 publications
2
46
0
Order By: Relevance
“…Cassava roots with high fibre content are typically less suitable for gari production (Mkumbira et al ., 2007). Overall, user preferences indicate that a good quality root for gari and fufu production was harvested at maturity, is medium to large in size, has high density and low water content, has a white bright colour, has smooth outer skin, and is not rotten and does not have foamy parts inside (Chijioke et al ., 2020; Ndjouenkeu et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Cassava roots with high fibre content are typically less suitable for gari production (Mkumbira et al ., 2007). Overall, user preferences indicate that a good quality root for gari and fufu production was harvested at maturity, is medium to large in size, has high density and low water content, has a white bright colour, has smooth outer skin, and is not rotten and does not have foamy parts inside (Chijioke et al ., 2020; Ndjouenkeu et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…That root color is far more important in the South West and North Central than in other regions can relate to the longer fermentation practiced in these regions, which can cause discoloration of the roots. In the other regions, gari is colored using red palm oil (Awoyale et al, 2021;Chijioke et al, 2021;Teeken et al, 2021). Teeken et al (2021) found that a variety disliked because of discoloration in the South West (where there is long fermentation) was not clearly disliked in the South East.…”
Section: Regional Differences Are Complex But Draw Lessons Important For Breedingmentioning
confidence: 99%
“…Nigeria has the highest cassava production globally (FAOSTAT, 2021), where it is grown both as a subsistence and as a cash crop. A collection of recent studies explored adoption drivers of cassava in Nigeria (Wossen et al, 2017), and trait preferences for cassava products (Chijioke et al, 2021;Ndjouenkeu et al, 2021;Teeken et al, 2021), including gender analysis of trait preferences (Teeken et al, 2018). The gender differences in trait preferences observed in these studies mainly reflect the gendered roles along the crop value chain.…”
Section: Introductionmentioning
confidence: 99%
“…Chijioke et al. (2021) reported that ease of forming a dough, thickness, and drawing‐ability of fermented wet fufu mash during cooking are the quality preferences for processed cassava products, and the attributes preferred by both men and women. The authors added that smoothness and ease of swallowing were preferred attributes for cooked fufu while being sticky, and intense aroma were less preferred in cooked fufu .…”
Section: Introductionmentioning
confidence: 99%
“…Sour taste, intense aroma, white color, and smooth texture are the quality characteristics and determinants of fufu acceptance (Bamidele et al, 2015). The variations in processing methods and differences in physicochemical properties of cassava varieties influence the texture and organoleptic properties of the cooked fufu (Chijioke et al, 2021). A study by Awoyale et al (2020) showed that consumer-preferred quality traits are the eventual determinants of the adoption decision of commercialized cassava farmers.…”
Section: Introductionmentioning
confidence: 99%